PENGARUH SERVICESCAPE DAN KEMAMPUAN KOMUNIKASI INTERPERSONAL KARYAWAN TERHADAP KEPUASAN KONSUMEN PADA WISATA ECO GREEN PARK BATU. - Putri, Luh Ayu Surya Eka; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study disscuses the servicescape and interpersonal comunication skills of employees that affect customer satisfaction tourism service. The purpose of this study was to determine whether the servicescape factors consisting of enviromental conditions, spatial layout, signs and symbol or artifacts and interpersonalÂ communication affects customer satisfaction and also to find out which factors are the most dominant influence on custumer satisfaction. The analytical method used is multiple regression analysis and classical assumption. As for testing the hypothesis using the F test and T test based on the analysis performed, variable ambient conditions (X1), spatial layout (X2), signs,Â symbol, artifacts (X3), and interpersonal communication skills (X4) jointly have a significant impact on customer satisfaction. Based on the T test is known that (X1), (X2), (X3), no significant effect partially while (X4) significant effect partially. Through standardized Î² coefficient obtained that variable interpersonal communication skills have a dominant influence in the amount of 0,544. Keywords: Servicescape, Interpersonal Communication, Satisfaction.